2024
DOI: 10.5334/joc.345
|View full text |Cite
|
Sign up to set email alerts
|

Michelangelo Effect in Virtual Sculpturing: Prospective for Motor Neurorehabilitation in the Metaverse

Simona Pascucci,
Giorgia Forte,
Elena Angelini
et al.

Abstract: We investigated the Michelangelo effect, i.e. the facilitatory effect of a virtual art therapy in motor rehabilitation (Iosa et al. 2021), with a novel virtual reality paradigm in which users are engaged in motor exercises with 3D sculptures. In particular, thirty young adults were immersed in a virtual environment where they could sculpt, by using the real hands, some famous sculptures in the history of art, such as the David of Michelangelo, the Venus of Milo and the statue of Laocoon and His Sons, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In fact, their performance and their perceived effort were not significantly different among the three conditions. Previous studies also reported this effect in healthy subjects during virtual paintings [6] and virtual sculpturing [16]. This difference could be explained by the fact that the digital memory game task proposed in this study was easier than the tasks tested in virtual reality.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…In fact, their performance and their perceived effort were not significantly different among the three conditions. Previous studies also reported this effect in healthy subjects during virtual paintings [6] and virtual sculpturing [16]. This difference could be explained by the fact that the digital memory game task proposed in this study was easier than the tasks tested in virtual reality.…”
Section: Discussionmentioning
confidence: 46%
“…Then, the perceived effort was not significantly correlated with the patient's memory, suggesting that the Michelangelo effect was generalized independently by the patient's mnemonic capacity. On the other hand, this effect was observed for virtual paintings [6], virtual sculpturing [16], and now, for memory card gaming, suggesting that it could be present in very different tasks.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In their paper, Pascucci and collaborators ( Pascucci et al, 2024 ) investigate the virtual embodiment in the context of the Michelangelo effect, wherein painting a virtual art masterpiece yields less fatigue and motor errors than colouring control canvas. In this study the authors prompted the participants to virtually sculpt either some famous sculptures in the history of art or some control stimuli, using their real hands digitally reproduced in the virtual environment.…”
mentioning
confidence: 99%